(untitled) (Research, Society and Development, 2021)
Syphilis is a systemic bacterial infection caused by Treponema pallidum, a spirochete and gram-negative bacterium, curable and exclusive to humans, however when treatment is not carried out in a timely manner, it can result in a chronic course with damage of irreversible potential. Thus, the objective of this study is to describe the performance of nursing, with the help of the multidisciplinary team, using the health education activity as a syphilis awareness and prevention strategy. This is a descriptive experience report, with a qualitative approach, carried out in a Municipal Health Unit in Ananindeua. According to experience, it was possible to observe, given the interaction, the primordiality of information in relation to syphilis, so that health education is essential for access to knowledge about diseases and demonstrated in practice how you can help the population to prevent and maintain the necessary care before the disease. Based on the actions provided, it is clear and necessary to observe the need to promote actions aimed at controlling the disease, including prevention and notification actions, active search and appropriate treatment.